2020
DOI: 10.3354/dao03453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a functional feed additive on mitigation of experimentally induced gilthead sea bream Sparus aurata enteromyxosis

Abstract: In gilthead sea bream Sparus aurata, infection by Enteromyxum leei produces a cachectic syndrome with anorexia, weight loss, severe epaxial muscle atrophy and, eventually, death. Currently, there are neither vaccines nor effective prescription medicines to control this infection. Nutraceutical approaches are raising interest in the aquaculture industry, responding to the lack of therapeutic tools for the management of insidious chronic losses due to parasites. In this study, the effect of a commercially availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…This parasite lives and divides in the intestinal epithelium inducing intestinal damage, impaired nutrient absorption and anorexia. Therefore, among the most common disease signs induced by this parasite are diminished growth and weight loss [ 62 ]. After 70 days, post-infection (dpi) biometric parameters showed that, as expected, the weight gain, relative to the weight at 0 dpi, of the control uninfected fish was significantly higher in the fast-growth family (12.6%) than in the low-growth group (4.7%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This parasite lives and divides in the intestinal epithelium inducing intestinal damage, impaired nutrient absorption and anorexia. Therefore, among the most common disease signs induced by this parasite are diminished growth and weight loss [ 62 ]. After 70 days, post-infection (dpi) biometric parameters showed that, as expected, the weight gain, relative to the weight at 0 dpi, of the control uninfected fish was significantly higher in the fast-growth family (12.6%) than in the low-growth group (4.7%).…”
Section: Resultsmentioning
confidence: 99%
“…For the parasite challenge, the sampling was performed 70 days post-infection (July 2018). All fish were starved for 48 h, sacrificed by overexposure to the anesthetic MS-222, weighted and the entire intestines were taken for parasite quantification by qPCR as previously described [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…This parasite lives and divides in the intestinal epithelium inducing intestinal damage, impaired nutrient absorption and anorexia. Therefore, among the most common disease signs induced by this parasite are diminished growth and weight loss [62]. After 70 days post-infection (dpi) biometric parameters showed that, as expected, the weight gain, relative to the weight at 0 dpi, of the control uninfected sh was signi cantly higher in the fast-growth family (12.6%) than in the low-growth group (4.7%).…”
Section: Genetic Background Effects On Disease Resistancementioning
confidence: 53%
“…For the parasite challenge, the sampling was performed 70 days post-infection (July 2018). All sh were starved for 48 hours, sacri ced by overexposure to the anesthetic MS-222, weighted and the entire intestines were taken for parasite quanti cation by qPCR as previously described [62]. Foundation (FPCM).…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…For the parasite challenge, the sampling was performed 70 days post-infection (July 2018). All sh were starved for 48 hours, sacri ced by overexposure to the anesthetic MS-222, weighted and the entire intestines were taken for parasite quanti cation by qPCR as previously described [62].…”
Section: Sampling Proceduresmentioning
confidence: 99%